The Polish National Minority in Germany in the Light of International Law - Sandorski, Jan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The paper is an English translation of the article “Polska mniejszość narodowa w Niemczech w świetle prawa międzynarodowego” published originally in Ruch Prawniczy, Ekonomiczny i Socjologiczny no. 2 from 2010. The text is published as a part of a section of the Adam Mickiewicz University devoted to the achievements of the Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.